Von Willebrand Factor multimers profiling with a semi‐automated system. Issue 6 (13th March 2013) - Pasotti, Fabio; Martini, Giuliana; Caimi, Luigi; Ricotta, Doris
<x xml:space="preserve">Abstract</x> Abnormalities in plasma von Willebrand factor (vWF) concentration and function result in von Willebrand disease (vWD). The diagnosis requires a battery of tests such as screening procedures, confirmatory tests, phenotypic characterization, and genotyping. The phenotypic testing (multimer pattern analysis) is important in order to subclassify the hereditary and the acquired forms of vWD. Only few laboratories are skilled to perform this analysis. The extreme range of protein size from 250 kDa monomer to over 20 000 kDa multimers requires a time‐consuming procedure (3–4 days) and presents many technical difficulties. To standardize the method and to overcome technical difficulties, we developed a rapid and sensitive semi‐automated method to visualize the multimeric structure of vWF. The semi‐automated method we present performs the electrophoresis of patient's plasma in 120 min on a precast gel. Gels are suitable for the G26 Interlab instrumentation. After gel blotting, the method allows visualization of the vWF multimer pattern directly on the membrane. We reduced the time required from 72 to 8 h and we propose this test for the first level screening of vWF multimer deficiency.